„Ülevalt anti märku“. Jutlustaja Ilse Katvel - Pilli, Toivo (Usuteaduslik Ajakiri, 2021)
„I Received Guidance from Above“: Preacher Ilse Katvel This article explores the life and ministry of Ilse Katvel (1906–1987), a female preacher. She was influenced by pietistic Lutheranism, holiness movement ideas, and Estonian free church spirituality. In 1934, she joined the Evangelical Christian Free Church in Narva, which had grown out of the Blue Cross movement in the area. After moving to the Saaremaa Island in 1944, she became a deacon and co-elder in a Pentecostal-background church in Valjala, which was part of the Union of Evangelical Christians-Baptists. Katvel became an influential Bible teacher who was invited to preach all across Estonia. The article argues that Katvel’s spiritual disciplines resemble the mystical-devotional lifestyle practised in different Christian traditions, including in Medieval piety – a commitment to work and prayer, fasting, living modestly, remaining unmarried, receiving food gifts, as well as being generous, and taking care of people in need. She and a group of like-minded „sisters“ devoted themselves to prayer, including prayers for healing. This group had an experiential openness to the work of the Holy Spirit. Katvel contemplated the relations between creation and the Creator, and images from nature helped her interpret spiritual realities. Cooperating with Christians from different denominational backgrounds and preaching both in Lutheran and free churches, she highlighted the unifying element of spirituality, focusing on Christcentredness and lived-out sanctification, which is present in a wide range of Christian traditions.